Nuclear protein in testis midline carcinoma of larynx: An underdiagnosed entity. Issue 8 (29th March 2016) - Kundra, Ajay; Andrei, Mirela; Westra, William; Chaudhry, Rashid; Moussouris, Harry; Gohari, Arash; Wang, Jen C.
Abstract: Background: Nuclear protein in testis (NUT) carcinomas are very rare and have a very poor survival rate. The most common sites of involvement include the nasal cavity, sinus, and mediastinum. Laryngeal NUT midline carcinoma is extremely rare, with only 2 cases reported thus far. Here, we are describing another case of NUT laryngeal carcinoma. Methods and Results: The patient was a light smoker and nondrinker who presented with upper respiratory tract obstruction. Imaging and laryngoscopic evaluation revealed a large intraluminal laryngeal mass. Biopsy demonstrated poorly differentiated carcinoma with intact mucosa and only focal coexpression of CK5/6 and p40. NUT protein immune‐stain positivity conclusively established the diagnosis of NUT midline carcinoma. Conclusion: Absence of well‐known risk factors, pathologic finding of lack of mucosal involvement and lack of squamous differentiation with poorly differentiated carcinoma, should prompt clinicians to consider this rare entity as a possible diagnosis. © 2016 Wiley Periodicals, Inc. Head Neck 38:E2471–E2474, 2016